Evaluation of static test used to predict the potential for acid drainage generation at sulphide mine sites - K. Adam; A. Kontopoulos; A. Kourtis; B. Gazea (The Institute of Materials, Minerals and Mining, 1905)
Static tests give a measure of the balance between acid-producing and acid-neutralising mineral components in a material, while kinetic tests determine acid generation and neutralisation over a long period. Drill-core samples from the amphibolite and gneiss host rocks of the Stratoni lead-zinc sulphide deposit in Greece and mine/mill waste samples from Stratoni and Olympias were examined by the standard acid base accounting, BCR and net acid production tests. Mineralogical data on the materials and resulting residues were used to illustrate the differences between the methods and establish their ranges of applicability. BCR seems to simulate most closely the conditions prevailing during generation of acid mine drainage but is time-consuming and requires elaborate equipment. Acid base accounting is suggested for standard screening; net acid production might be used in the field or for solids with less than 10% S